The power of the family - Alberto Alesina; Paola Giuliano (Institute for the Study of Labor (IZA), 2007)
The structure of family relationships influences economic behavior and attitudes. We define our measure of family ties using individual responses from the World Value Survey regarding the role of the family and the love and respect that children need to have for their parents for over 70 countries. We show that strong family ties imply more reliance on the family as an economic unit which provides goods and services and less on the market and on the government for social insurance. With strong family ties home production is higher, labor force participation of women and youngsters, and geographical mobility, lower. Families are larger (higher fertility and higher family size) with strong family ties, which is consistent with the idea of the family as an important economic unit. We present evidence on cross country regressions. To assess causality we look at the behavior of second generation immigrants in the US and we employ a variable based on the grammatical rule of pronoun drop as an instrument for family ties. Our results overall indicate a significant influence of the strength of family ties on economic outcomes.
urn:nbn:de:101:1-20080402249
Keywords: 330; Familienökonomik; Familiensoziologie; Gemeinschaft; Wirtschaftswachstum; Welt